THE EFFECTS OF HIGH INTENSITY INTERVAL TRAINING ON CLINICAL SYMPTOMS AND FUNCTIONAL CAPACITY IN ADULTS WITH NEUROMUSCULAR DISEASE. Issue 11 (9th October 2013) - Jones, Katherine; Whittaker, Roger; Miller, James; Jakovljevic, Djordje; Turnbull, Doug; Gorman, Grainne
Abstract : Background: Neuromuscular disease includes a spectrum of inflammatory and mitochondrial myopathies where dysfunction in the energy–producing mitochondria can cause muscle weakness, exercise intolerance and fatigue. Continuous endurance training has been shown to improve cardiorespiratory fitness but disease symptoms also limit many patients' ability to perform such exercise. Aim: To determine the effects of low volume, high intensity interval training (HIIT) on clinical symptoms and functional capacity in adults with sporadic Inclusion Body Myositis and mitochondrial myopathies. Methods: Subjects with a clinical diagnosis of mitochondrial disease or sporadic Inclusion Body Myositis completed 16 weeks of the HIIT, where short bursts of high intensity exercise were followed by low intensity, recovery intervals. Exercise tolerance (i.e. peak oxygen consumption and work rate), muscle and whole body composition, electrical activity in muscle and disease burden were assessed before and after exercise intervention. Results: Preliminary results from seven subjects (65±10 years of age) show an improvement in peak exercise VO2 (1.3l/min±0.3 to 1.4l/min±0.4, p=0.296) and a significant increase in peak work capacity following HIIT (95±28 to 107±34 watts, p=0.036). For two subjects, muscle electrical activity during voluntary contraction decreased by more than 50% after HIIT, however, there was no significant change in peak muscle strength or symptoms of fatigue. There was also no significant change in bone mineral density with HIIT although one subject with mitochondrial disease was found to have marked osteopenia prior to, and after exercise intervention. Conclusion: Preliminary findings suggest that high intensity interval training improved aerobic work capacity in patients with mitochondrial myopathies and sporadic Inclusion Body Myositis without exacerbating symptoms of fatigue. However, Macro–EMG findings did identify possible denervation in one subject with sporadic Inclusion Body Myositis following HIIT. Further investigations and analyses will help to better characterise subjects' disease burden and assess the wider safety implications and therapeutic potential of exercise in neuromuscular disease.